A cavity-mediated collective quantum effect in sonoluminescing bubbles. (November 2015) - Beige, Almut; Kim, Oleg
Abstract: This paper discusses a collective quantum effect which might play an important role in sonoluminescence experiments. We suggest that it occurs during the final stages of the collapse phase and enhances the heating of the particles inside the bubble.